Rethinking the Reasons of Greenhouse Gases Emission in ASEAN Countries: Finding Reasons in Urbanization, Industrialization and Population Growth - Tarasawatpipat, Chaisri; Mekhum, Witthaya (International Journal of Energy Economics and Policy, 2020)
Recently, more of the greenhouse gases emission has been seen within ASEAN countries. Basically, there are different factors that can cause greenhouse gas emissions. Some of the reasons of greenhouse emission can be industrialization, urbanization, population growth, manufacturing processes, energy consumption etc. In this research paper, the impact of urbanization, industrialization, population growth on greenhouse gases emission has been analyzed. This analysis has been done in the context of Brunei, Laos, Cambodia, Indonesia, Myanmar, Malaysia, Philippines, Vietnam, Singapore and Thailand – the ASEAN countries. The methodology used for the analysis is the bootstrap panel causality test, LM panel test of co-integration, panel unit root test of Pesaran and Shin that permit cross-sectional dependency. The outcomes of the research have proposed that hypothesis of emission of greenhouse gases is valid in Vietnam, Indonesia and Laos. However, these factors play less significant role in greenhouse gas emission in Philippines, Malaysia and Myanmar. These factors have some impact over greenhouse gas emission in Brunei, Cambodia and Singapore too. Based on the overall analysis given in the research, it can be stated that urbanization, industrialization and population growth do have an impact over the greenhouse gas emission. Keywords: Greenhouse Gas Emission, Gross Domestic Product, Urbanization, Industrialization, Population Growth JEL Classifications: P25, O14 DOI: https://doi.org/10.32479/ijeep.10688